2016
DOI: 10.1038/srep35219
|View full text |Cite
|
Sign up to set email alerts
|

Structures, properties, and energy-storage mechanisms of the semi-lunar process cuticles in locusts

Abstract: Locusts have excellent jumping and kicking abilities to survive in nature, which are achieved through the energy storage and release processes occurring in cuticles, especially in the semi-lunar processes (SLP) at the femorotibial joints. As yet, however, the strain energy-storage mechanisms of the SLP cuticles remain unclear. To decode this mystery, we investigated the microstructure, material composition, and mechanical properties of the SLP cuticle and its remarkable strain energy-storage mechanisms for jum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Using CLSM for assessing the material composition, as in this study, allows for the detection of areas with different material properties and for a detailed understanding of the material distribution [ 3 , 11 , 18 ]; this knowledge can be transferred to computer models used in FEM [ 16 , 51 ]. Although CLSM does not allow for a precise measurement of the properties of the identified materials, the information on the material distribution can be used as a template for targeted nanoindentation or atomic force microscopy (AFM) [ 3 , 46 ], which in turn can be employed to refine finite-element or other models.…”
Section: Discussionmentioning
confidence: 99%
“…Using CLSM for assessing the material composition, as in this study, allows for the detection of areas with different material properties and for a detailed understanding of the material distribution [ 3 , 11 , 18 ]; this knowledge can be transferred to computer models used in FEM [ 16 , 51 ]. Although CLSM does not allow for a precise measurement of the properties of the identified materials, the information on the material distribution can be used as a template for targeted nanoindentation or atomic force microscopy (AFM) [ 3 , 46 ], which in turn can be employed to refine finite-element or other models.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the main purpose of jumping for adult locusts is to achieve a sufficient initial speed for initiating flight [17], the fact that the take-off speed did not change among the different ground types revealed that the jump behaviors of the locust were robust on various substrates. The kinetic energy of the locust jump was primarily released from the elastic strain energy stored by the SLP cuticle during the extension of the hind leg [3,4]. The similar mass-specific kinetic energy for the jumps on the three ground types meant that the stored strain energy was not wasted by the somewhat useless extension arising from the slip or insertion of tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Their jumps serve several critical functions: to escape from predators, to achieve an initial velocity for flight, and provide a more rapid alternative to travel than crawling. The locust jump has been extensively studied, especially its postural control, the mechanics of the hind leg, patterns of muscle and motoneuron activity, and mechanisms of energy storage and release [2][3][4][5][6][7][8][9][10][11]. The action of jumping in locusts is fueled by their hind legs in the following steps: initial flexion of the tibiae, co-contraction of the flexor and extensor muscles, and rapid tibial extension after trigger activity [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insect cuticle, also known as the exoskeleton, is the outermost part of the insect body, it serves a variety of functions such as sensory perception of the environment, means of locomotion [36], maintain the physical structure of the organism, the foregut, hindgut, tracheal system and apodemes [37], and protection from desiccation, moreover, the cuticle also serves as the rst and major barrier against external adverse compounds penetration [38]. So, the cuticle is a major route of insecticide penetration in insects, insect cuticles are composed of cuticular protein, chitin and lipids, in fact, the properties of insect cuticle including permeability to pyrethroids are in uenced not only by the chitin sclerotization, construction, and hydration, but also by the regular combinations of different cuticular proteins and their arrangements [38,39], recent protein-level and gene-level analyses have demonstrated a surprising diversity of cuticular proteins within and amongst species [40].…”
Section: Discussionmentioning
confidence: 99%